2009
DOI: 10.1002/hep.22793
|View full text |Cite
|
Sign up to set email alerts
|

Association between hypothyroidism and hepatocellular carcinoma: A case-control study in the United States #

Abstract: Thyroid hormones play an essential role in lipid mobilization, lipid degradation, and fatty acid oxidation. Hypothyroidism has been associated with nonalcoholic steatohepatitis; however, the association between thyroid diseases and hepatocellular carcinoma (HCC) in men and women has not been well established. We investigated the association between hypothyroidism and HCC risk in men and women in a case-control study, which included 420 eligible patients with HCC and 1104 healthy controls. We used multivariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
129
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 151 publications
(135 citation statements)
references
References 38 publications
6
129
0
Order By: Relevance
“…Clinical hypothyroidism seems to be a risk factor for several neoplasias such as liver cancer, thyroid malignancies, high-grade glioblastomas and human breast cancer (Reddi et al 2007, Polyzos et al 2008, Hassan et al 2009, Angelousi et al 2012. In contrast, increased TH levels have been associated with higher risk of esophageal, thyroid, breast and ovarian cancer development (Turkyilmaz et al 2005, Rasool et al 2014, Kunjumohamed et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical hypothyroidism seems to be a risk factor for several neoplasias such as liver cancer, thyroid malignancies, high-grade glioblastomas and human breast cancer (Reddi et al 2007, Polyzos et al 2008, Hassan et al 2009, Angelousi et al 2012. In contrast, increased TH levels have been associated with higher risk of esophageal, thyroid, breast and ovarian cancer development (Turkyilmaz et al 2005, Rasool et al 2014, Kunjumohamed et al 2015.…”
Section: Discussionmentioning
confidence: 99%
“…34 A recent epidemiological study also suggested that long-term hypothyroidism is positively correlated with HCC incidence, independent of other risk factors. 35 However, the proposed tumor-suppressor role of TRs remains a subject of controversy. For example, an animal model of colorectal tumorigenesis revealed that TRα1 positively regulates several molecules downstream of the Wnt signal, consequently facilitating the expression of β-catenin/Tcf4 target genes and enhancing cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Recent report showed that hypothyroidism was associated with a high risk of HCC in women (Hassan et al, 2009) (Kress et al, 2010). However, TRa1 when specifically overexpressed in the intestinal epithelium is unable to induce cancer development.…”
Section: Discussionmentioning
confidence: 99%